Oxidative stress, telomere shortening, and DNA methylation in relation to low‐to‐moderate occupational exposure to welding fumes. (27th May 2015) - Li, Huiqi; Hedmer, Maria; Wojdacz, Tomasz; Hossain, Mohammad Bakhtiar; Lindh, Christian H.; Tinnerberg, Håkan; Albin, Maria; Broberg, Karin
<x xml:space="preserve">Abstract</x> Evidence suggests that exposure to welding fumes is a risk factor for lung cancer. We examined relationships between low‐to‐moderate occupational exposure to particles from welding fumes and cancer‐related biomarkers for oxidative stress, changes in telomere length, and alterations in DNA methylation. We enrolled 101 welders and 127 controls (all currently nonsmoking men) from southern Sweden. We performed personal sampling of respirable dust and measured 8‐oxodG concentrations in urine using a simplified liquid chromatography tandem mass spectrometry method. Telomere length in peripheral blood was measured by quantitative polymerase chain reaction. Methylation status of 10 tumor suppressor genes was determined by methylation‐sensitive high‐resolution melting analysis. All analyses were adjusted for age, body mass index, previous smoking, passive smoking, current residence, and wood burning stove/boiler at home. Welders were exposed to respirable dust at 1.2 mg/m3 (standard deviation, 3.3 mg/m3; range, 0.1–19.3), whereas control exposures did not exceed 0.1 mg/m3 (P < 0.001). Welders and controls did not differ in 8‐oxodG levels (β = 1.2, P = 0.17) or relative telomere length (β = −0.053, P = 0.083) in adjusted models. Welders showed higher probability of adenomatous polyposis coli (APC) methylation in the unadjusted model (odds ratio = 14, P = 0.014), but this was not significant in the fully adjusted model (P = 0.052). Every working year as a welder was associated with 0.0066 units shorter telomeres (95% confidence interval −0.013 to −0.00053, P = 0.033). Although there were no clear associations between concentrations of respirable dust and the biomarkers, there were modest signs of associations between oxidative stress, telomere alterations, DNA methylation, and occupational exposure to low‐to‐moderate levels of particles. Environ. Mol. Mutagen. 56:684–693, 2015. © 2015 Wiley Periodicals, Inc.